The performance of nickel-loaded lignite residue for steam reforming of toluene as the model compound of biomass gasification tar. Issue 6 (December 2018) - Xiao, Xianbin; Liu, Ji; Gao, Anni; Zhouyu, Mengqiu; Liu, Binghan; Gao, Manda; Zhang, Xiaolei; Lu, Qiang; Dong, Changqing
Abstract: Tars should be removed from biomass gasification systems so as not to damage or clog downstream pipes or equipment. In this paper, lignite insoluble residue (LIR) after extraction of humic acids was used as the support to prepare a nickel-loaded LIR (Ni/LIR) catalyst. This novel catalyst Ni/LIR was tested in steam reforming of toluene as a model compound of biomass tar conducted in a laboratory-scale fixed bed reactor. When compared to the reactions without catalyst or with Ni/Al2 O3, Ni/LIR was confirmed as an active catalyst for toluene conversion at a relatively low temperature of 900 K. The investigated reforming parameters during the experiments in this research were selected as reaction temperature at a range of 850–950 K, steam/carbon molar ratio at a range of 2–5 mol/mol, and a space velocity from 1696 to 3387 h −1 . It was concluded that, under optimum conditions, significant amount of syngas yields, acceptable Ni/LIR consumption and more than 95% of toluene conversion can be obtained from the biomass Ni/LIR catalytic gasification system. Highlights: Lignite residue was used as the support to prepare a nickel-loaded catalyst. This novel catalyst is low cost and combined catalytic activity from the inherent mental species. Nickel particles were highly dispersed with satisfactory loading amount by the combined ion exchange and impregnation method. This novel catalyst tested in steam reforming of toluene, more than 95% of toluene conversion obtained.